Factors affecting the microbiological load of Italian hunted wild boar meat (Sus scrofa). (February 2020) - Orsoni, Francesca; Romeo, Claudia; Ferrari, Nicola; Bardasi, Lia; Merialdi, Giuseppe; Barbani, Roberto
Abstract: This study investigates the microbiological conditions before maturation of wild boar meat ( Sus scrofa ) processed in approved game handling establishments in Italy. Fillets and legquarters of 37 carcasses were tested to assess Aerobic Colony Count (ACC), Enterobacteriaceae Count (EC) and Salmonella presence. Salmonella was never found and mean values of ACC and EC were 4.67 ± 1.78 SD and 2.60 ± 1.58 SD log CFU/cm 2, respectively. Both ACC and EC increased with time between evisceration and skinning, were significantly higher in fillets and when meat was processed by untrained operators. ACC also increased with boars' weight and when carcasses were cleaned with running potable water. Based on limits set by EU Regulation No 1441/2007 for pork meat, most legquarters resulted satisfactory or acceptable (59% for ACC and 70% for EC), while most fillets were unsatisfactory (76% ACC, 78% EC). Results show that the wild game meat supply chain can be a safe process when handling practices reported in European and National regulations are met. Highlights: Legquarters microbiological load was mostly within the EU limits set for pork meat. None of the samples showed Salmonella contamination. Washing with running water worsens the microbiological quality of carcasses. Microbial contamination increases with time between evisceration and skinning. Correct training of operators reduces microbial contamination.